WGCNA-based analysis of MYL2 and its relationship with muscle fiber development during the embryonic stage in Inner Mongolia Albas White Cashmere Goats - Wu, Danni; Xu, Xiaolong; Zhao, Dan; Qin, Qing; Zhang, Chongyan; Gao, Jiale; Xing, Anru; Lv, Qi; Zhang, Haijun; Liu, Zhihong (Frontiers in Veterinary Science, 2025)
The weight and quality of skeletal muscle are important indicators of meat product quality in livestock. The development of muscle fibers mainly occurs during the embryonic period, with the later stages of embryonic development being the critical time for muscle fiber formation. This stage determines postnatal growth rate, developmental traits in adulthood, and meat production performance. Therefore, studying the tissue structure and developmental patterns of muscle fibers during the embryonic period is crucial. This study utilized Weighted Gene Co-expression Network Analysis (WGCNA) to analyze the transcriptomes of goat skeletal muscle at 10 developmental stages during fetal development. A total of 10 co-expression modules were identified, with the blue module being selected for its relevance to embryonic development and muscle growth in the later stages of fetal development. Functional enrichment analysis revealed that this module is associated with mitochondrial processes (such as the tricarboxylic acid cycle and ATP synthesis) and is enriched in muscle-related pathways, including AMPK, Wnt, MAPK, and FoxO signaling pathways. The protein–protein interaction (PPI) network identified four key genes (MYLPF, MYL2, PFKM, and TCAP). The expression patterns of these four differentially expressed genes (MYLPF, MYL2, PFKM, and TCAP) identified in the network were validated through RT-qPCR, and the results showed a high consistency with the sequencing data. Immunohistochemical analysis confirmed that MYL2 expression increased continuously, with the strongest positive staining observed in the cytoplasm during the later stages of muscle fiber development. These findings provide new insights into muscle fiber development and skeletal muscle growth in cashmere goats.